Bipolar-I Depression Outpatient Treatment Quality and Costs in Usual Care Practice - Busch, Alisa B. (2008)
OBJECTIVE: To examine the longitudinal usual care quality and costs of bipolar-I depression treatment in adults. EXPERIMENTAL DESIGN: Observational study of claims data from a privately insured population, ages 18−64, diagnosed with bipolar-I depression (N=925), treated in 1999 and 2000, examining depressed phase specific and annualized treatment quality (receipt of antimanic medication and/or psychotherapy). Treatment costs were calculated and stratified by quality. PRINCIPAL OBSERVATIONS: Little more than half (56%) of the patients diagnosed with bipolar-I depression received both an antimanic agent and psychotherapy during their acute phase depression treatment, whereas fifteen percent received an antimanic agent without psychotherapy. Eighteen to 28% of spending was accounted for by treatment that did not meet the standards of practice guidelines—and two-thirds to three-quarters of it was treatment that included an antidepressant without an antimanic agent (care that is advised against by guidelines). CONCLUSIONS: Considerable resources were spent in care inconsistent with guidelines—much of that was care that could worsen the course of bipolar illness. This provides an opportunity for policy makers to develop mechanisms of quality improvement that redirects a substantial proportion of resource dollars to care that is more efficacious. Further, when conducting quality assessment and examining outcomes using administrative data, hospital admissions alone are an inadequate measure of bipolar disorder affective instability in claims data.